Analisis Kualitas Pelayanan Perjalanan Jamaah Umrah Pada PT. Anugrah Quba Mandiri Kota Bengkulu - Satriawan, Satriawan; Mursalin, Supardi; Makmur, H. (ITB AAS Indonesia Surakarta, 2024)
This research aims to find out the quality of service provided by PT. Quba Mandiri's gift from Bengkulu City to Umrah pilgrims. The type of research used is field research (Field Research) with a qualitative approach. This research shows the results that Reliability, Responsiveness, Physical Evidence, Empathy and Credibility at PT. Anugrah Quba Mandiri has been said to be good because it has guided the Umrah pilgrimage series reliably, is responsive in serving administration, the facilities are as promised, cares for Umrah pilgrims by providing a sense of security free from danger and risk by providing accident and health insurance. and the credibility of PT. AQM needs to be improved again by looking at the financial transactions carried out by the congregation so that no party feels disadvantaged.